JESUS OF NAZARETH: PARADIGM PAR EXCELLENCE - Pathrapankal, Joseph (Journal of Dharma, 1992)
The real identity of this Jesus of Nazareth has been a topic that had been •discussed over several centuries, right from the time of his appearance in Galilee. For some it was question coupled with contempt : "Isn't he the carpenter?" (Mk 6:3), whereas for others he was very different from the scribes because he was teaching with authority (Mt 7:29). While his enemies accused him of having Beelzebub in him (Mk 3:22), his disciples exclaimed with wonder: "what kind of man is this? Even the winds and the waves obey him" (Mt 8:27). According to John, the person of Jesus was widely discussed among the Jews: Some said, "This man is really the prophet," while others said, "he is the Messiah" (Jn 7:40), and there was a dispute over this among the people (Jn 7:42-44). The guards who were sent to arrest Jesus, returned saying: "Nobody has ever talked the way this man does" (Jn 7:46). Many Jews and even Herod thought that he was John the Baptist come back to life, while others said that he was Elijah or one of the prophets of long ago